Repercussões do ato infracional e da privação de liberdade para adolescentes e familiares - Brondani, Renata Petry (2019)
This dissertation research sought to investigate the repercussions of compliance with the socio-educational measure of committal through the perception of adolescents and relatives. In order to achieve the proposed objectives, it was made use of qualitative research, while the delimitation of the present research was the Study of Multiple Cases. The data collection occurred through documental research as well as through individual interviews semi-structured with five adolescents fulfilling a socio-educational measure of committal, and one relative of each of these adolescents, totalizing ten participants. The analysis of the data obtained was done through the technique of synthesis of crossed cases. From the results, it was revealed that the socio-educational measure of committal has a significant impact on family relationships, and the physical detachment showed, paradoxically, a potential to promote rapprochement and re-signification of the relationships and bonds among the family. The maternal figure manifested itself as the most relevant one in the adolescent's life trajectory, being exalted and valued by them. Moreover, the suffering and the need to speak coming from the interviewed mothers was noticed, and later concluded that they had become emotionally stronger from coping with the fragilities that arose. Another aspect discussed in this study was the relevance given by the participants to the institutional arrangements that allow family communication in the context of deprivation of liberty: visiting days and correspondences. It was also possible to discuss the fear and anguish that permeated the exit of the institution because said space had a protective appeal and represented a relent of turbulent environments considering the "outside world" seemed to not be welcoming. Given these data, it was reinforced the importance of effective participation and integration with families in the units of compliance with the socio-educational measure of committal.